The Living from the Dead : Disaffirming Biopolitics - Murray, Stuart J. (RSA series in transdisciplinary rhetoric., 2022)
"Presents a rhetorical critique of contemporary neoliberal biopolitics through a series of transdisciplinary case studies"--